BOGDANOV-TAKENS BIFURCATIONS IN THREE COUPLED OSCILLATORS SYSTEM WITH ENERGY PRESERVING NONLINEARITY - Owen, Livia; Tuwankotta, J.M. (Journal of the Indonesian Mathematical Society, 2012)
looked at pdf abstractDOI :Â http://dx.doi.org/10.22342/jims.18.2.113.73-83